Pengaruh Kepatuhan Melaksanakan Shalat Berjamaah terhadap Peningkatan Kedisiplinan dan Rasa Tanggung Jawab - Hisny Fajrussalam; Astri Mulyani; Puja Sahwa Anisa; Sofi Kamilatus Sadiah; Wiwin Winengsih (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Education is very important to create better human resources, education should be carried out seriously and responsibly, because it is a process that is directed towards forming maturity in humans. Schools are the most appropriate place for the government to realize the creation of national education aimed at the nation's children. Schools must also provide rules to students in order to create a discipline during the learning process to be achieved. This research was conducted to find out how to train the habit of increasing discipline in the learning process. In this study the instruments and data collection tools that the authors use are 1) laptops, 2) mobile phones, 3) social media/internet. The collection technique was carried out using qualitative methods, namely by distributing questionnaires. The data collection technique was carried out by distributing a set of written questions to the respondents to be answered. The results obtained from this study are congregational prayers have an effect on increasing discipline and a sense of responsibility, so it can be concluded that a person can increase his discipline and sense of responsibility slowly through habituation of congregational prayers on a regular basis.